Tinjauan Kinerja Layanan dan Kepuasan Penumpang Angkutan Penyeberangan Pure - Raha - Lakawa, Irwan; Hujiyanto, Hujiyanto; Syamsuddin, Syamsuddin; Razmi Noris, Muhamad (Universitas Sulawesi Tenggara, 2024)
The Pure-Raha ferry port in Southeast Sulawesi Province is a port that serves passenger and goods crossings connecting the mainland of Buton Island and Muna. Good service quality is one of the determining factors for the company's success. The research method is structured through interviews with respondents by answering the questions in the questionnaire. The analysis used uses Importance Performance Analysis (IPA) and Customer Statistics Index (CSI). The research results show that the consumer satisfaction index for the service performance of the Pure-Raha ferry port in Southeast Sulawesi Province is 0.71. This shows that consumers are satisfied with the quality of port services by 71%. However, the management needs to create a special queue for motorbike riders.